Helicobacter pylori: Beginning the Second Decade - Ann Matisko; ABR Thomson (Canadian Journal of Gastroenterology)
‘Beginning the Second Decade’ - a recent international meeting on Helicobacter pylori - was held in conjunction with the VIIth International Workshop on Gastroduodenal Pathology and H pylori and with the meeting of the European Helicobacter pylori Study Group in Houston, Texas from September 30 to October 1, 1994. A menu of 476 abstracts, published in the American Journal of Gastroenterology (1994;89:8), highlighted the explosion of advances in this area. The Houston meeting was followed by the Tenth World Congresses of Gastroenterology from October 2 to 7, 1994 in Los Angeles, California, again with scores of presentations and posters on topics ranging from the epidemiology of H pylori infection to steps towards the development of a human vaccine. All this was in addition to important new work presented earlier in 1994 in New Orleans during Digestive Diseases Week. In this digest of these important meetings, the authors will not regurgitate what the informed reader already knows, but will instead focus on the recent developments in important areas, providing selected key published references for background, and referring to this new work in abstract form which is at the cutting edge of “yesterday’s tomorrow today”.